2015
DOI: 10.1080/23312521.2015.1087933
|View full text |Cite
|
Sign up to set email alerts
|

Is Depression a Sin or a Disease? A Critique of Moralizing and Medicalizing Models of Mental Illness

Abstract: Moralising accounts of depression include the idea that depression is a sin or the result of sin, and/or that it is the result of demonic possession which has occurred because of moral or spiritual failure. Increasingly some Christian communities, understandably concerned about the debilitating effects these views have on people with depression, have adopted secular folk psychiatry's 'medicalising' campaign, emphasising that depression is an illness for which, like (so-called) physical illnesses, experients sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
(18 reference statements)
0
8
0
1
Order By: Relevance
“…It was not evident that focus group participants saw people with mental illness as demonstrating heroism, as experiencing greater freedom through their limitations, or as "strangers in our midst," as Webb (2012) puts it. Similarly, participants did not state that mental illness offered opportunities for transformation (Scrutton, 2016) or that people with mental illness could be comforted by God's willingness to be one who suffered by dying on the cross (Scrutton, 2015). The absence of these ideas suggests that views of mental illness within the church could be furthered by providing theological concepts that might contradict prevailing stereotypes and prejudices.…”
Section: Interface Of Study Findings With Scholarly Literaturementioning
confidence: 96%
See 2 more Smart Citations
“…It was not evident that focus group participants saw people with mental illness as demonstrating heroism, as experiencing greater freedom through their limitations, or as "strangers in our midst," as Webb (2012) puts it. Similarly, participants did not state that mental illness offered opportunities for transformation (Scrutton, 2016) or that people with mental illness could be comforted by God's willingness to be one who suffered by dying on the cross (Scrutton, 2015). The absence of these ideas suggests that views of mental illness within the church could be furthered by providing theological concepts that might contradict prevailing stereotypes and prejudices.…”
Section: Interface Of Study Findings With Scholarly Literaturementioning
confidence: 96%
“…Yet, rather than simply viewing mental illness as a hardship to be overcome, it is important to also recognize that mental health challenges offer opportunities for deeper spirituality. Those who suffer from mental illness can take comfort in God's own ability to suffer, including God's willingness to die on a cross (Scrutton, 2015). Christians can experience comfort in knowing God understands their pain.…”
Section: Views Related To Belonging and Hospitalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between demonic aetiologies of mental illness, religious shame, and lowered support-seeking is supported by Scrutton (2015), Hartog and Gow (2005), and Nearchou et al (2018), who found that solely spiritual views of mental illness act to discourage religious individuals from seeking psychological treatment. Moreover, individuals may avoid treatments which are not based on prayer or scriptural study (Stanford, 2007).…”
Section: Agency and Treatmentmentioning
confidence: 99%
“…Stump argues that the reason for Christ's separation from God is that the overwhelming pain of sharing in the suffering of humanity prevents closeness and attention sharing with God whilst Christ is on the cross. For another example of how physical or emotional pain may cause an experience of separation from God, see Scrutton (2015), an analysis of a Christian approach to depression.…”
Section: Notesmentioning
confidence: 99%